2019
DOI: 10.1152/ajpcell.00189.2018
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a-5p enhances radiosensitivity in hepatocellular carcinoma through replication protein A3-induced activation of the DNA repair pathway

Abstract: Hepatocellular carcinoma (HCC) is known for its high mortality rate worldwide. Based on intensive studies, microRNA (miRNA) expression functions in tumor suppression. Therefore, we aimed to evaluate the contribution of miR-146a-5p to radiosensitivity in HCC through the activation of the DNA damage repair pathway by binding to replication protein A3 (RPA3). First, the limma package of R was performed to differentially analyze HCC expression chip, and regulative miRNA of RPA3 was predicted. Expression of miR-146… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 33 publications
5
24
0
Order By: Relevance
“…Previous studies have reported that certain pharmaceutical molecules, including corylin, melatonin and gefitinib in combination with irinotecan, were able to enhance cancer cell sensitivity to chemotherapy by inhibiting RAD51-induced DNA repair in HCC (78)(79)(80). Luo et al (81) observed increased expression of RAD51 in HCC tissues, consistent with the findings of the present study, and revealed that miRNA-146a-5p enhanced the radio-sensitivity of HCC cells via the DNA repair pathway. However, studies have not yet reported an association between miR-139-5p and RAD51 regulation in patients with HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported that certain pharmaceutical molecules, including corylin, melatonin and gefitinib in combination with irinotecan, were able to enhance cancer cell sensitivity to chemotherapy by inhibiting RAD51-induced DNA repair in HCC (78)(79)(80). Luo et al (81) observed increased expression of RAD51 in HCC tissues, consistent with the findings of the present study, and revealed that miRNA-146a-5p enhanced the radio-sensitivity of HCC cells via the DNA repair pathway. However, studies have not yet reported an association between miR-139-5p and RAD51 regulation in patients with HCC.…”
Section: Discussionsupporting
confidence: 92%
“…RPA can inhibit DNA repair pathway [190], and then promote tumor cell growth and resist apoptosis in radiotherapy of liver cancer. After radiotherapy, miR-146a-5p expression was raised in HCC cells, while RPA expression was suppressed, and the DNA repair pathway was activated to promote the sensitivity to radiotherapy [191]. Similarly, the decrease of miR-29b level and the increase of phosphatase and tensin homologous protein (PTEN) expression in residual tumor cells happened after radiotherapy for cervical cancer.…”
Section: Resistance With Dna Damage Repair-related Genesmentioning
confidence: 99%
“…Its role in inflammation is less well studied but has been suggested to be a potential biomarker for rheumatoid arthritis [53][54][55]. Furthermore, similar to rheumatoid arthritis patients, miR-146a-5p expression levels are reduced in hepatocellular cell carcinoma [56]. miR-146a is involved in B cell hyperplasia [57], and miR-146a-5p has been reported to be a useful prognostic biomarker for DLBCL [58].…”
Section: Discussionmentioning
confidence: 99%